ChemInform Abstract: Synthesis of New Phosphahelicene Scaffolds and Development of Gold(I)‐Catalyzed Enantioselective Allenene Cyclizations. Issue 3 (29th December 2015) - Aillard, Paul; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract: Four new gold complexes containing a phosphahelicene scaffold are prepared and endo‐(P)‐(I) is found to be the most efficient one.